Mining Stress Distribution and Gas Drainage Application of Coal Seam Group under Fault Influence - Meng Tang; Xiangtao Kang; Jiachi Ren; Lin Gao; Zhenqian Ma; Dezhong Kong (Geofluids)
The existence of fault structures often seriously endangers the safe production of coal mines. In order to ensure the safe and efficient production of close coal seam group mines under the influence of faults, it is of wide engineering significance to study the gas occurrence and extraction technology between coal seam groups under the influence of faults. In this study, the mining and gas drainage of 13817 working face in Yueliangtian Mine were taken as the research background. Combined with theoretical research, laboratory analysis, and numerical simulation analysis, the pressure relief range of coal seam and the evolution characteristics of surrounding rock stress were studied, the coal and gas comining system under the influence of faults was determined, the gas drainage technology was optimized, and the effect was investigated and analyzed. The results show that the gas pressure reduction zone is formed in the range of 20 m and 6 m of the lower wall of F1 fault, and the pressure relief effect is good in the range of 40 m above the roof of the working face to 20 m below the bottom plate during the advancing process. The optimized gas drainage technology has a good effect on gas control in coal seam group mining under the influence of faults. The absolute gas emission of the working face is reduced to 28~36 m3/min, the gas concentration in the upper corner of the mining face is about 0.6%, and the gas concentration of the return airflow is reduced to less than 0.5%. The gas extraction rate of No. 8 coal seam is 52.9%, and the gas content in the fault zone is reduced by 60%, realizing the safe and efficient comining of coal and gas. The research results have certain reference and application value for mine gas control with similar mining conditions.